Atención de la urgencia en casa: una reacción automática (2009)
ABSTRACT: Understanding the meaning of actions done by patient’s family members at home when an emergency situation happened and were waiting for medical attention. Methodology: the particularization ethnographic approach was used. The information was gathered from interviews and observations made to people that received emergency attention at home, in the city of Medellín-Colombia between January 2005 and December 2006. Results: In emergency situation people delivery tasks automatically among who are next to the patient, these tasks are done to recover health, to give company to avoid patient’ suffering and to organize physical space and prepare patient to receive medical attention. Conclusion: it is essential to provide education to community for people’s automatic reactions in case of emergency at home to develop safe and calmed actions.